Impact Evaluation of Ogun State Bureau of Employment Generation Intervention Programmes (2012)
Unemployment and employment generation have attracted the interests of governments and other stakeholders of many nations. Governments at all levels in Nigeria have introduced various unemployment intervention programmes which have not achieved total result. Among such are the intervention programmes of the Bureau of employment generation (BEG) in Ogun State since 2003. While these employment generation programmes (EGPs) of BEG have been internally assessed, there has not been an external assessment. Therefore, this study evaluated the impact of the employment generation programmes of BEG (Agricultural training, vocational training and Ogun state unemployed graduates scheme) on employment generation in Ogun State, Nigeria. The study adopted descriptive survey research design. Multi-stage sampling technique was employed to select 2,560 respondents: 525 agricultural training graduates, 650 vocational training graduates, 1,325 Ogun State Unemployed Graduates Scheme (OGUGRADS) beneficiaries, 28 staff of BEG and 32 trainers of the programmes. Graduates and trainers were connected using the data base of the Bureau. Data were collected using Employment Generation Programmes Questionnaire (r = 0.69) and, Staff and facilitators/Trainers Questionnaire (r = 0.71). These were complemented with 19 sessions of Focus Group Discussions (FGD) for graduates and 25 sessions of Key Informant Interview (KII) for staff and trainers. Eight research questions were answered and six hypotheses tested at 0.05 significance level. Data were analysed using percentages, Pearson Product Moment Correlation, Multiple regressions, and content analyses. The employment generation programmes (EGPs) of BEG had significant joint effect on poverty reduction (F(3,2496)= 2651.84, p<0.05) accounting for 76% of the variations in the dependent measure. Their relative effects on poverty reduction are as follows: OGUGRADS (= 0.844, p<0.05), vocational training (= 0.127, p<0.05) and agricultural training (= 0.008, p<0.05). The EGPs also have a significant joint effect on social-vices reduction (F(3,2496)= 3625.96, p<0.05) with 81% variations in the dependent measure. Their relative effects on social-vices are: OGUGRADS (= 0.904, p<0.05), vocational training (= 0.41, p<0.05) and agricultural training (= 0.069, p<0.05). The components of the EGPs of BEG had significant joint effect on employment generation (F(6,2493)= 334.46, p<0.05); and accounting for 45% in the variations of the dependent measure. Significant relationship existed between funding of the BEG programmes and employment generation (r = 0.281, p < 0.05). Significant relationship also existed between EGPs and establishment of small-scale enterprises (r = 0.357, p<0.05) and entrepreneurship (r = 0.555, p<0.05). The FGD and KII results revealed that though the BEG, through its EGPs, has impacted positively on the graduates and their communities, its programmes are impeded by funding, maintenance, coordination and monitoring. The Ogun state Bureau of Employment Generation has improved employment generation, reduced poverty and social-vices, but has been limited by financial, technical and managerial constraints. Government should, therefore, ensure more funding, effective coordination and monitoring of the EGPs for the Bureau to impact more on the lives of the people of Ogun State.